2011
DOI: 10.1186/1743-422x-8-275
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of HBV and HBV vaccination coverage in health care workers of tertiary hospitals of Peshawar, Pakistan

Abstract: BackgroundHepatitis B Virus (HBV) may progress to serious consequences and increase dramatically beyond endemic dimensions that transmits to or from health care workers (HCWs) during routine investigation in their work places. Basic aim of this study was to canvass the safety of HCWs and determine the prevalence of HBV and its possible association with occupational and non-occupational risk factors. Hepatitis B vaccination coverage level and main barriers to vaccination were also taken in account.ResultsA tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
39
5
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 19 publications
8
39
5
2
Order By: Relevance
“…Similar results of higher Anti-HCV antibody positivity were found among older HCWs [18]. Another study found that the age and employment duration strongly correlated with HBV prevalence [23]. Recently, a study carried out in Poland found that HBV occurred most frequently during the periods of 15-19, 20-24 and 25-29 years of employment (50% of cases), and it was lower for women than for men by 1.71 years (18.2 years versus 19.9 years) [37].…”
Section: Occupationsupporting
confidence: 87%
See 1 more Smart Citation
“…Similar results of higher Anti-HCV antibody positivity were found among older HCWs [18]. Another study found that the age and employment duration strongly correlated with HBV prevalence [23]. Recently, a study carried out in Poland found that HBV occurred most frequently during the periods of 15-19, 20-24 and 25-29 years of employment (50% of cases), and it was lower for women than for men by 1.71 years (18.2 years versus 19.9 years) [37].…”
Section: Occupationsupporting
confidence: 87%
“…In contrast, we observed lower prevalence rates than those found in Syria (6%), Cameroon (23.6%), Nigeria (13%), Pakistan (2.18%) and Uganda (8.1%) [20][21][22][23][24]. Anti-HBc, HBeAg and Anti-HBe antibodies were found in 8.5%, 0.7% and 8.0%, respectively.…”
Section: Occupationcontrasting
confidence: 82%
“…11 Also, in Nigeria the coverage was 47.7% in medical students 12 and 37.9% among dental students. 13 Not only were these disappointing results restricted to medical students alone, but generally the health care workers vaccination coverage was low in other studies in Pakistan (37.2%), 14 South Africa (19.9), 15 and Egypt (15.8%), 16 whereas the vaccination coverage was 76.6% among the medical students and 46.7% among interns in Palestine, 12 and another high coverage (80.5%) reported among dentists in a recent study in KSA. 17 As regards the immune status in our students, only 15.2% proved to have protective titer with their HBs Ab > 10 iu/ml.…”
Section: Discussionmentioning
confidence: 92%
“…The HBV infection has a high worldwide prevalence and about 6% of HCWs are exposed to it annually (4). In developing countries NSSIs cause a high infection rate of 40% to 60% among HCWs; vaccination, however, has reduced the HBV infection rate to less than 10% in developed countries (5).Although HBV infection is a vaccine-preventable disease, the rate of immunization in high-risk groups is lower than the expected rate.…”
Section: Introductionmentioning
confidence: 99%